Islamic Education Strategies in Addressing Radicalism and Intolerance in School Environments - Ibnu Abirul Choir; Komarudin Sassi (CV. Creative Tugu Pena, 2025)
Radicalism and intolerance represent serious challenges to national cohesion and religious harmony, particularly within school environments where the character and worldview of younger generations are shaped. This study examines the role of Islamic educational strategies in preventing and countering radical and intolerant tendencies in school settings. Employing a qualitative approach through a comprehensive literature review, the study analyzes scholarly works related to Islamic education, radicalism, and intolerance. The findings reveal that Islamic education plays a strategic role in fostering moderate, tolerant, and inclusive attitudes by strengthening the principle of rahmatan lil ‘alamin, implementing contextual and value-based learning, promoting teachers as moral role models, and integrating Islamic values holistically into the curriculum. In addition, effective collaboration among schools, families, and communities is crucial in creating a safe and supportive educational environment free from extremist influences. This study contributes to the existing literature by providing a conceptual framework for integrating Islamic educational values as a preventive mechanism against radicalism and intolerance in schools, offering practical insights for educators and policymakers in promoting peaceful and harmonious social coexistence. Overall, Islamic education, when strategically implemented, can serve as a strong foundation for safeguarding students from radical ideologies while nurturing a culture of peace and mutual respect in society.